Exportación de bebidas naturales de néctar a base de maracuyá con pitahaya, a Países Bajos, Holanda, Ámsterdam - Ynfanzon Alvarez, Carlos Alexis (2019)
The current research work pursues the commercialization of natural nectar drinks based on passion fruit and pitahaya. These fruits are sown in Peru and have very good health benefits which leads us to have an important strength in the face of competition. The plan aims to be able to market our natural drink in the Dutch market. That is why, to achieve this goal, the company Dalex Natural S.A.C is created, where it will begin to do the research of the target market and then go on to inquire about the possible suppliers of these two valuable fruits. The selected suppliers are an important part of our export process, which is why they were carefully selected. Through this study we consider that export is the way in which we will reach customers with high demand in consumption of natural drinks such as the European market. That is why, we saw the need to investigate Peruvian exports to European markets to see the behavior that has been having the export of natural drinks. Consequently, after having studied the different markets of Europe, the country of Holland became the target country being the city of Amsterdam. Likewise, our target customers will be the distributors of beverages in the Dutch market this because we are still beginners in this market and this form of income generates less risk.